Design of an Immunization Information System for Monitoring the Achievement of Child Immunization Coverage - Prakoso, Bakhtiyar Hadi; Yunus, Muhammad; Suyoso, Gandu Eko Julianto; Vestine, Veronika (International Journal of Healthcare and Information Technology, 2026)
Immunization is one of the most effective public health interventions in preventing infectious diseases and reducing mortality and morbidity in the global population, with the potential to prevent 3 to 3.5 million deaths each year from vaccine-preventable diseases. In Low- and Middle-Income Countries (LMICs), including Indonesia, vaccination coverage for children under five years old still shows low numbers.  The low vaccination coverage is partly caused by the use of manual recording systems, which leads to delays in decision-making processes in immunization management. This study seeks to address this issue by developing a UI/UX prototype design for a toddler immunization information system. The proposed UI/UX design is equipped with features to monitor and record immunization activities in a particular region in real time, enabling effective, accurate, and integrated decision-making and implementation of immunization programs at both regional and national levels. The UI/UX design was developed using the User-Centered Design (UCD) method, which actively involves users throughout the process. Usability testing was conducted using the System Usability Scale (SUS) method. The results indicate that the designed UI/UX meets the standard requirements of public health centers and achieves satisfactory outcomes from prospective users. The contribution of this research is the proposed UI/UX design for immunization monitoring. In the future, this UI/UX design can serve as a foundation for the development of an Immunization Monitoring Information System.